Preventive Interventions for Speech Development in Preschool Children. Research Report - Danuta Grzesiak-Witek; Katarzyna Pająk (Edukacja Elementarna w Teorii i Praktyce, 2025)
Preschool age is a period of intensive language development. The aim of the study was to assess the quality of prevention of speech disorders in preschoolers and to verify the knowledge of speech therapists on the preventive strategies used during speech development. The specific features of the study required the use of a diagnostic survey method, which allowed for assessing social awareness as well as investigating the opinions and views of speech therapists.